Pengaruh intervensi pemerintah terhadap kinerja keuangan dengan efisiensi sebagai variabel intervening - Haderianor, Haderianor; Rizani , Fahmi; Rasidah, Rasidah (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze more deeply: the effect of government intervention on the efficiency and financial performance of PDAMs, the role of efficiency in mediating the effect of government intervention on the financial performance of PDAMs. The sample of this research is 12 PDAMs in South Kalimantan with the unit of analysis, namely performance evaluation reports for six consecutive years in 2015-2020. The data analysis technique in this study uses Partial Least Square (PLS) with a calculation process assisted by the Smart PLS 3.29 application program. The results showed that government intervention in the form of equity participation had no significant effect on cost efficiency and financial performance in terms of cash ratios, billing effectiveness and solvency. However, government intervention has a significant effect on production efficiency and financial performance on the ROE aspect. The results also show that cost efficiency has a significant effect on financial performance in the ROE aspect and does not significantly affect the billing effectiveness, cash ratio, and solvency aspects. There is a significant effect of production efficiency on financial performance on the aspect of billing effectiveness, but no significant effect on the aspects of ROE, cash ratio, and solvency. Cost efficiency does not mediate the effect of government intervention on financial performance. Meanwhile, production efficiency can mediate the effect of government intervention on financial performance on the aspect of billing effectiveness, but cannot mediate on the aspects of ROE, cash ratio, and solvency